Operating Room Delays between “Time-in OT” and Skin Incision During Spine Surgery at a Tertiary Care Hospital - Kashif, Aleena; Sami Ur Rehman; Malik, Arij; Kashif, Zeeshan (Indus Journal of Bioscience Research, 2025)
Background: The operating room is a very important component of any tertiary health-care institution. An adequately managed operating room results in increased surgical turnover as well as patient satisfaction. Delay in surgery start time is surgery starting later than the scheduled time. Delay in starting scheduled surgical procedure is a reflection of operating room inefficiency. Objective: To determine the frequency of surgical delays among patients undergoing spine surgeries and various factors causing operating room delays in spine surgeries between ’time-in OT’ to skin incision. Material and Methods: This is a cross-sectional study done at Orthopedics department, Doctors Hospital, Lahore from 15 May 2023 to 15 November 2023. Patients’ aged 12 to 75 undergoing elective spine surgeries were included. Data collection involved noting ’time-in-OT’ upon patient entry and recording the duration of various preparatory steps, including IV line securing, monitor attachment, anesthesia induction, and patient positioning. Delays due to staff or equipment unavailability were also documented. The total time from OT entry to skin incision was then calculated and recorded. Data was analyzed in SPSS. Results: The mean age of 46.5 years (±15.5) and an age range of 21 to 75 years. Delays in the operating room were observed in 47% of patients, with the mean time from entering the OT to skin incision being 65.2 minutes (±30.5). Key factors contributing to delays included missing paperwork (7.4%), lack of patient preparation (8.5%), staff unavailability (8.5%), surgeon unavailability (20.2%), and anesthetist unavailability (12.8%). Other significant causes of delay were on-table review (11.7%), airway assessment (18.1%), time required for attaching monitors (9.6%), intubation (48.6%), acquiring additional venous access (26.6%), maintaining arterial line (50.0%), and patient positioning (64.9%). Conclusion: The conclusion of the study, that Operating room delays in spine surgeries were common, primarily due to missing paperwork, preparation, and equipment setup. No significant differences were observed across age, BMI, or ASA groups, indicating these are systemic issues requiring improved coordination and processes.